2017
DOI: 10.1016/j.ttbdis.2016.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Novel genotype of Ehrlichia canis detected in samples of human blood bank donors in Costa Rica

Abstract: This study focuses on the detection and identification of DNA and antibodies to Ehrlichia spp. in samples of blood bank donors in Costa Rica using molecular and serological techniques. Presence of Ehrlichia canis was determined in 10 (3.6%) out of 280 blood samples using polymerase chain reaction (PCR) targeting the ehrlichial dsb conserved gene. Analysis of the ehrlichial trp36 polymorphic gene in these 10 samples revealed substantial polymorphism among the E. canis genotypes, including divergent tandem repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 30 publications
4
62
1
2
Order By: Relevance
“…18,20,21 Genotypic variations of E. canis has also recently been observed in human blood donors in Costa Rica with serological evidence of zoonotic transmission that share a resemblance to the Brazilian strains. 22 The possibility of distinct genotypes of E. canis causing different clinical manifestation could lead to difficulty in diagnosing canine or human ehrlichiosis. 19,20 Based on the close proximity between domestic dogs and humans, dogs may serve as a sentinel for zoonotic vector-borne diseases in Peru as similarly described in Venezuela.…”
Section: Introductionmentioning
confidence: 99%
“…18,20,21 Genotypic variations of E. canis has also recently been observed in human blood donors in Costa Rica with serological evidence of zoonotic transmission that share a resemblance to the Brazilian strains. 22 The possibility of distinct genotypes of E. canis causing different clinical manifestation could lead to difficulty in diagnosing canine or human ehrlichiosis. 19,20 Based on the close proximity between domestic dogs and humans, dogs may serve as a sentinel for zoonotic vector-borne diseases in Peru as similarly described in Venezuela.…”
Section: Introductionmentioning
confidence: 99%
“…Both human granulocytic ehrlichiosis (HGE) and human monocytic ehrlichiosis (HME) caused by E. canis have been reported, albeit in low incidence. Bouza‐Mora et al () reported a 3.6% incidence rate of E. canis from samples of blood donors in Costa Rica. Likewise, another incident of human ehrlichiosis was recently reported in Mexico by Sosa‐Gutierrez et al (), which eventually led to the death of a 32‐year‐old patient, who had previously presented with a history of fever, chills, muscle aches, malaise, headache and loss of appetite for over 10 days.…”
Section: Discussionmentioning
confidence: 99%
“…Perez, Bodor, Zhang, Xiong, and Rikihisa () reported the first case of human ehrlichiosis from six patients in Venezuela, and E. canis was implicated as the causative agent through molecular analysis of their blood samples, as the E. canis strains recovered from their blood samples were genetically identical with those from canine. E. canis is distributed worldwide; hence, the presence of known competent arthropod vectors ( Amblyomma and Rhipicephalus species) and natural reservoir hosts ( Odocoileus virginianus ), to a large extent, determine the distribution of this pathogen (de la Fuente, Estrada‐Pena, Venzal, Kocan, Sonenshine, ; Bouza‐Mora et al, ). This study reported the detection of E. canis genetic material from ticks collected from sheep and goat.…”
Section: Discussionmentioning
confidence: 99%
“…La EMC es una enfermedad infecciosa causada por la bacteria Ehrlichia canis, considerada zoonótica (16,17) y emergente, transmitida principalmente por la garrapata del perro (Riphicephalus sanguineus) (18). La etiología de la EMC surge a raíz de la infección por bacterias Gram-negativas del género Ehrlichia (aunque las tinciones con gram no suelen ser útiles) clasificadas dentro del orden de los Rickettsiales y la familia Anaplasmataceae (15).…”
Section: E H R L I C H I a C A N I S Y E F E C T O D E Doxiciclina Enunclassified
“…CME is an infectious disease caused by the Ehrlichia canis bacterium, which is considered to be zoonotic (16,17) and emergent, transmitted mainly by the dog tick (Riphicephalus sanguineus) (18) phagocytophilum) en ejemplares caninos y de igual manera su detección en los vectores conocidos (19)(20)(21).…”
Section: Ehrlichia Canis and The Effects Of Doxycycline In The Treatmentmentioning
confidence: 99%